On the Effects of Group Identity in Strategic Environments - Chloé Le Coq; James Tremewan; Alexander K. Wagner (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2014)
We examine differences in behavior between subjects interacting with a member of either the same or different identity group in both a centipede game and a series of stag hunt games. We find evidence that subjects interacting with outgroup members are more likely to behave as though best-responding to uniform randomization of the partner. We conclude that group identity not only affects a player's social preferences, as identified in earlier research, but also affects the decision making process, independent of changes in the utility function.
Keywords: C72; C91; C92; D83; 330; Group identity; centipede game; steg hunt game; experiment